Effect of topical administration of Tropicamide 1% on intraocular pressure - قبيلي براءة; قحطان جلول; محمود رجب (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: To assess the effect of Mydriasis with tropicamide1% on intraocular pressure. Material and Methods: This cross-sectional study included 104 eyes of 70 patients in the age group of 18-60 years. known cases of glaucoma, closed angle, operated cases and eye disorders were excluded. After taking detail history and examination, IOP was measured then tropicamide 1% was instilled. After mydriasis IOP was again measured. Data was collected and analyzed on SPSS 21. Means of IOP was compared before and after dilatation. Results: We had104 eyes of 70 patients in which 18 (25.7%) were males and 52(74.3%) were females. Their mean age was 40.2 ± 13.4 Emmetropic eyes were 22 (21.2%) and hypermetropic eyes were 50 (48.1%) and myopic eyes were 32(30.8%). Mean base line IOP before dilatation was 13.43±0.9 and after dilatation was13.6± 0.5 . The means of IOP before and after dilatation was compared in emmetropes with myopes and hypermetropes. Conclusion: There was no statistically significant difference in intraocular pressure after mydriasis with tropicamide 1%. Keywords: Mydriasis, intraocular pressure, tropicamide.